Sirosporium diffusum associado à nogueira-pecã: patogenicidade, morfofisiologia, filogenia e escala diagramática - Poletto, Tales (2018)
The culture of the pecan [Carya illinoinensis (Wangenh.) K. Koch], family Juglandaceae, have economic importance in southern Brazil and cultivation grows rapidly. Consequently, the increase of planted area has triggered frequent epidemics, mainly of fungal diseases, which are favored by the climate and the accumulation of susceptible hosts. Recently, a new disease was diagnosed and reported in Brazilian plantations [(POLETTO et al., 2017), https://doi.org/10.1094/PDIS-06-16-0820-PDN], which is caused by fungi Sirosporium diffusum. The disease causes defoliation of the plants, reducing the production of fruits. In view of this observation, the objective of this work was to evaluate the pathogenicity of isolates of Sirosporium sp. associated with brown leaf spot of the pecan, characterize them morphological, physiological, and molecular, as well as to develop a disease diagrammatic scale for epidemiological studies. For that, samples of symptomatic leaves were collected in 10 pecan orchards, in the state of Rio Grande do Sul. After obtaining the 10 isolates of the pathogen, a pathogenicity test was conducted for the evaluation of the incidence and virulence of the pathogen, characterized morphologically and the variables used in the UPGMA (Method of grouping the mean distance) analysis in which the isolates were grouped in a dendrogram according to the morphological dissimilarity and the characters that contributed the most to the divergence were established. Molecular analysis was performed by amplifying and sequencing the ITS and tef1- regions of the DNA. For physiological characterization, eight culture media and five light regimes were combined in the first assay, while in the second, the three best treatments from the first assay which conferred higher sporulation were combined with three temperatures. For the elaboration of the diagrammatic scale, 240 symptomatic leaflets were collected, from which the real severity of the disease was obtained in percentage terms. For the construction of the scale, the observed limits of minimum and maximum disease severity plus six intermediate levels were used. The validation was performed by eight evaluators, first without and, subsequently, with the use of the scale. The results showed through the pathogenicity test that all isolates were pathogenic and the incidence was 100% for most of them, with differences in the virulence capacity. The phylogenetic analysis confirmed the isolates as Sirosporium diffusum, the causative agent of the brown leaf spot in C. illinoinensis in Brazil. Sequencing of the ITS region and the tef1- gene were effective for identification of the fungus as S. diffusum. The best artificial conditions of culture in which S. diffusum shows good mycelial growth and sporulation together was obtained with photoperiod of 24 hour, temperature of 20 ±1°C and culture media V8CaCO3 or CA. The diagrammatic scale proposed for evaluation of brown leaf spot in C. illinoinensis provides good accuracy, precision and reproducibility of the estimates to the evaluators, besides being easy to use, and epidemiological studies of the disease are adequate.